The hafsidRoots of the ottoman functions and surnames in Near and Middle maghreb - boulainine, Nassima; kouicem, Mohammad (The Algerian Historical Journal, 2026)
In thispaper, we deal with the functions and titles during the Ottoman epoch in the Near Maghreb (Libya and Tunisia) and the Middle Maghreb (Algeria) and there roots in the Hafsidepoch, namely: the Makhzen, the mahalla, the shawish, the mezwar, the Qaid, the sheikh, the mufti, the judge, the adoul, the notary and the emir of the pilgrimage ride and the preacher and imam. The study reached several results, functions and titles, referenced by Hafsid, whoruled the Near Maghreb (Libya and Tunisia now) and the eastern part of the Middle Maghreb (Algeria) up to Bejaia and Tubna(Barika) in Batna region